Correlation Study of Student Learning Motivation in Civics Subjects in High School - Ali Akbar (Journal of Social Knowledge Education (JSKE), 2023)
Purpose of the study: The purpose of this study was to find out how the description of the school environment and the description of students' learning motivation in Civics subjects and the influence of the school environment on students' learning motivation in Civics subjects at SMA Negeri 6 Pandeglang. Methodology:The approach used in this research is a quantitative approach. The population in this study were all students majoring in social studies at SMA Negeri 6 Pandeglang, totaling 436 students. The sample used in this study was 82 students majoring in social studies at SMA Negeri 6 Pandeglang. The instruments used in this study were the school environment instrument and the student learning motivation questionnaire. The data analysis technique in this study is the correlation method with product-moment correlation and regression. Main Findings: The research results obtained by product moment correlation analysis, which has a sig value. 0.408 > 0.05 and the relationship level is 40.8%, meaning that the effect is at a moderate level of relationship. Furthermore, in the regression analysis, namely Y' = 59.040 + 0.339X and obtained a tcount of 3.986 > ttable 1.663 stating that H0 is rejected and Ha is accepted. Novelty/Originality of this study: There is an influence of the school environment on students' learning motivation in Civics subjects